Safe Human-Inspired Mesoscopic Hybrid Automaton for Longitudinal Vehicle Control. Issue 27 (2015) - Iovine, A.; Valentini, F.; Santis, E. De; Benedetto, M.D. Di; Pratesi, M.
Abstract: In this paper a mesoscopic hybrid automaton is introduced in order to obtain a human-inspired based adaptive cruise control. The proposed control law fits the design target of replacing and imitating a human driver behaviour. A microscopic hybrid automaton model for longitudinal vehicle control based on human psycho-physical behavior is first presented. Then a rule for changing time headway on the basis of macroscopic quantities is used to describe the interaction among all next vehicles and their impact on driver performance. Simulation results show the advantage of the mesoscopic model. A feasibility analysis of the needed communication network is presented.